PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PENIPUAN YANG DILAKUKAN OLEH TRADING FOREX - Isyma Eka Nurmardani; Abraham Ferry Rosando (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Forex (Foreign Exchange) or Foreign Currency is defined as foreign currency and other means of payment. Forex is used to conduct or finance international financial economic transactions and has an official exchange rate record at the central bank. Forex (Foreign Exchange) or better known as Foreign Exchange is a type of trade or transaction that trades the currency of one country against the currency of another country. Forex trading involves major money markets in the world for 24 hours continuously with a high level of liquidity and acceleration of price movements. Agreements in forex trading transactions are based on Article 1320 of the Indonesian Civil Code. These provisions are less effective, considering that there are still many illegal brokers, who do not have licenses, and companies that have bad intentions with the intention of deceiving investors. Because the Commodity Futures Trading Act has not fully regulated the forex trading system. This research aims to examine legal protection for consumers against fraud committed by forex trading. The research method used is a statute approach, conceptual approach, and case approach. Data collection through legislation, books, publications, journals and research results